Kualitas Pelayanan Samsat Keliling: Studi Kasus Pelayanan Pajak Kendaraan Bermotor Di Kabupaten Blora - Aris Toening Winarni; Susan Yuda Pamungkas (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This research aims to describe and analyze the quality of Mobile Samsat services in paying Motor Vehicle Tax (PKB) in Blora Regency. The quality of Mobile Samsat services is evaluated based on eight indicators, namely tangibles, accountability, transparency, reliability, responsiveness, assurance, empathy and participativeness. The research results show that overall, Mobile Samsat services in Blora Regency have been implemented well. However, the tangible dimension is still not optimal, especially related to the lack of seats provided for taxpayers queuing. Furthermore, researchers also analyzed six dominant factors that influence service quality, namely awareness, rules, organization, income, ability and service facilities. Of these six factors, service facilities are still an obstacle in the implementation of Mobile Samsat services. This can be seen from the limited electricity resources, the insufficient number of seats, and the stability of the internet network which is an obstacle in the service process. In general, the quality of Mobile Samsat services in Blora Regency is good, but service facilities need to be optimized so that public services can be carried out more optimally. This research provides important implications for Mobile Samsat service providers to pay more attention to aspects of service facilities and infrastructure, so that they can improve overall service quality and increase public satisfaction in paying motor vehicle tax. Apart from that, this research can also be a reference for local governments in developing and improving the quality of public services, especially in the context of motor vehicle tax payments. With the existence of quality Mobile Samsat services, it is hoped that it can encourage community compliance in fulfilling its tax obligations, so that it can increase regional income and support development in Blora Regency.